Digital Marketing Strategy to Increase Tourist Visits at Tri Muara Karang Waterfall (Case Study of Tri Muara Karang Waterfall in Belitas Seberang Village, Sindang Kelingi District, Rejang Lebong Regency) - Lisa Indriani; Adi Sismanto (Penerbit ADM, 2023)
Research on Tri Muara Karang Waterfall tourism, Belitar Seberang Village, Sindang Kelingi Regency. Rejang Lebong with the formulation of the problem What is the Digital Marketing Strategy to increase visits to the Tri Muara Karang Waterfall tour, Belitar Seberang Village, Kec. Sindang Kelingi Kab. Rejang Lebong? The population of 15 children used in this study were all employees who worked on the Tri Muara Karang Waterfall tour, Belitar Seberang Village, Kec. Sindang Kelingi Kab. Rejang Lebong amounted to 15 respondents. The sampling technique used total sampling based on predetermined criteria totaling 15 respondents. Observation data collection techniques, documentation and open questionnaires to visitors. Based on the results of the research that has been carried out, the managers, Village Officials, Tourism Office, Regional Government, especially Rejang Lebong Regency and Visitor Data on Tri Muarakarang Waterfall Tourism. It is necessary to increase supporting facilities and infrastructure in the management of Tri Muarakarang Waterfall Tourism. The role of the community, the government strongly supports the progress of the Tri Muarakarang Waterfall Tourism object in improving its quality and attractiveness. Increase the opinion of the community around the Tri Muarakarang Waterfall Tourism object, especially women both crafts and special food umkm that make visitors interested. Increasing the role of promotion either through websites or liplets, billboards and signboards will provide a strong advantage for visitors. Increased safety and comfort for visitors needs to be improved so that more visitors will come The increase in family tourism at this time will increase if the Tri Muarakarang Waterfall Tourism object is safe and smooth. As well as the discussion using the IFAS and EFAS methods in Table 4.1, namely the IFAS matrix, shows a score for strengths of 1.1 while for weaknesses of 0.9 so that the total weighted score obtained is 2.0. If the strengths and weaknesses are optimized, it will overcome the various weaknesses that exist. This is indicated by the total score on the IFAS matrix of 1.1 ≥ 0.9, which means that internal conditions have the power to overcome situations.